Review of IoT and electronics enabled smart agriculture - Gatkal, Narayan Raosaheb; Nalawade, Sachin Madhukar; Sahni, Ramesh Kumar; Bhanage, Girishkumar Balasaheb; Walunj, Avdhoot Ashok; Kadam, Pravin Bhaskar; Ali, Musrrat (International Journal of Agricultural and Biological Engineering, 2024)
The population increases at an exponential rate as human society advances, and pollution is increasingly depleting the availability of resources such as water and land. All these problems are thought to require the use of smart agriculture. By reducing chemical fertilizers and pesticides use, smart agriculture could mitigate land pollution and increase the sustainability of agricultural practices while also greatly enhancing the agro-ecological environment, yield, and quality of crops. The steps to make agriculture smart are possible by using data and communication technology, which helps with automatic operation and cultivation. Moreover, advances in wireless communication protocols will bring agriculture to a more intelligent stage. This study provides an overview of IoT technology and its application into the smart agriculture industry to make crop production automatic and intelligent by assessing their architecture (IoT devices, communication technologies, and processing), their applications, and research timelines. The communication protocols that have established uses in agriculture are reviewed first in this article. Various wireless communication protocols such as WiFi, ZigBee, SigFox, LoRa, RFID, NFMI, Terahertz, NB-IoT were summarized and their application in various field were also studied. These protocols in smart agriculture can effectively and efficiently address environmental data, water saving, monitoring animal behavior, accuracy, power efficiency, cost reduction due to low power consumption, accuracy, wide transmission, simple in operation and cost effective. Also, the most common microcontrollers used is Arduino (To develop autonomous machine), Raspberry pi (To store data) and 8-bit microcontroller (Process data). In addition, it is important to take advantage of modern communication technology to enhance crop production. Additionally, it examines the future opportunities and trends for IoT applications in smart agriculture, along with the ongoing challenges and issues that need addressing. Furthermore, this study provides crucial insights and guidance for future research and the development of IoT solutions. These advancements aim to improve agricultural productivity and quality while facilitating the transition to a more sustainable agroecological future. Keywords: IoT, smart agriculture, microcontroller, sensor, SigFox, LoRa, ZigBeeDOI: 10.25165/j.ijabe.20241705.8496Citation: Gatkal N R, Nalawade S M, Sahni R K, Bhanage G B, Walunj A A, Kadam P B, et al. Review of IoT and electronics enabled smart agriculture. Int J Agric & Bio Eng, 2024; 17(5): 44-57.